The girl from the other side : Siúil, a Rún. Vol. 9 - Nagabe; MacFarlane, Ysabet Reinhardt (Seven Seas Entertainment, 2020)
Teacher has lost himself, becoming just another wandering Outsider. At first, Shiva doesn't want to believe, but as she realizes she's been forgotten, she falls into despair. Will the two of them ever truly connect again? Meanwhile, the truth of the world--and the machinations of gods--begins to come to light within the Inside. Humanity makes a choice. A little girl makes a choice. Their actions lead the way to a future that must not come to pass.